HUBUNGAN PENERAPAN TRIAGE DENGAN RESPONSE TIME PERAWAT DIRUANG INSTALASI GAWAT DARURAT - chrisyen damanik (Jurnal Medika : Karya Ilmiah Kesehatan, 2018)
Background: The increasing number of hospital visitors every year is extremely influenced by the quality of comprehensive and good nurse care. By applying triage management, the patients with a life-threatening emergency level can be immediately handled. This research aimed to identify the correlation between the application of triage and the response time of nurses in the emergency department of Pertamina Hospital Balikpapan. Method: This research applied quantitative method with cross sectional design. The sample was taken by using total sampling technique with the total of 20 respondents. The data were collected by using observation sheet and analyzed by using Pearson test. Research Findings: The research findings showed that the p value was 0.01 (p<0.05) which indicated that there was a correlation between the application of red triage and the response time. The p value of yellow triage on the response time was 0.75 (p>0.05), which indicated that there was no correlation between the application of yellow triage and the response time. Conclusion: The research findings showed that in the application of red triage, Ha was accepted, indicating that there was a correlation between the application of red triage and response time. On the contrary, in the application of yellow triage, H0 was accepted, indicating that there was no any significant correlation between the application of yellow triage and the response time of the nurses. It is suggested to apply triage based on the category of patients’ condition so the risk of death can be prevented.